Bedside repair of congenital upper eyelid entropion: A variation of the Quickert suture technique - Naomie J. Warner; Barry N. Wasserman; Yu-Hung Lai (American Journal of Ophthalmology Case Reports, 2016)
Purpose: The current literature is void of any lasting bedside treatments for congenital upper eyelid entropion repair. Observations: A six-day old male was born with bilateral upper eyelid entropion associated with a duplication of the long arm of chromosome 3q11.1-q24. Conservative management with ocular lubrication and observation did not yield spontaneous resolution, and surgical intervention was performed at the bedside with a Quickert suture technique. Conclusions and importance: We discuss the novel use of this technique and review the relevant literature. Our technique is something not previously described in the literature for congenital upper eyelid entropion. It obtained satisfactory and sustained resolution.